TEKNIK KONSERVASI TANAH LAHAN KERING UNTUK MENGATASI DEGRADASI LAHAN PADA DESA MOJOREJO, LAMONGAN - Erfandi, Deddy (Bumi Lestari; Vol 13 No 1 (2013))
Abstract Soil conservation is one important aspect in supporting food security program. It is necessary to create an area that has a sustainable environment. Mojorejo Village, District Modo, Lamongan, East Java, has an area of ± 1,406 ha. Most of the area is dry land agro-ecosystem including upland lowland dry climate. Topography is undulating to hilly with deep and rocky limestone solum. In creating a sustainable environment, research has been conducted in the village on system conditions of dryland soil conservation techniques to address land degradation. The study aims to look at the soil conservation and soil conservation technologies recommended in situ, in order to address land degradation. Observations suitability for some commodities show that land can be developed for agricultural commodities in the village square Mojorejo 878.02 ha (92.56%), while the remaining area of 70.54 ha (7.22 %) could not be developed for agriculture because of the form settlement and land biophysical conditions do not allow. There is a potential source of water to irrigate rice fields allowed. On mixed farms that have slopes of 8-15%, the maximum proportion of annual crops is 50 % with a permanent stone terracing, while mixed farms on the slopes of 15-25%, the maximum proportion of annual crops is 30% with a permanent stone bench terraces.
Keywords: Key words: Technique of soil conservation, land degradation, dryland, Lamongan